Effectiveness and cost-effectiveness of mindfulness-based cognitive therapy compared with maintenance antidepressant treatment in the prevention of depressive relapse or recurrence (PREVENT): a randomised controlled trial. Issue 9988 (4th July 2015) - Kuyken, Willem; Hayes, Rachel; Barrett, Barbara; Byng, Richard; Dalgleish, Tim; Kessler, David; Lewis, Glyn; Watkins, Edward; Brejcha, Claire; Cardy, Jessica; Causley, Aaron; Cowderoy, Suzanne; et al.
Summary: Background: Individuals with a history of recurrent depression have a high risk of repeated depressive relapse or recurrence. Maintenance antidepressants for at least 2 years is the current recommended treatment, but many individuals are interested in alternatives to medication. Mindfulness-based cognitive therapy (MBCT) has been shown to reduce risk of relapse or recurrence compared with usual care, but has not yet been compared with maintenance antidepressant treatment in a definitive trial. We aimed to see whether MBCT with support to taper or discontinue antidepressant treatment (MBCT-TS) was superior to maintenance antidepressants for prevention of depressive relapse or recurrence over 24 months. Methods: In this single-blind, parallel, group randomised controlled trial (PREVENT), we recruited adult patients with three or more previous major depressive episodes and on a therapeutic dose of maintenance antidepressants, from primary care general practices in urban and rural settings in the UK. Participants were randomly assigned to either MBCT-TS or maintenance antidepressants (in a 1:1 ratio) with a computer-generated random number sequence with stratification by centre and symptomatic status. Participants were aware of treatment allocation and research assessors were masked to treatment allocation. The primary outcome was time to relapse or recurrence of depression, with patients followed up at five separate intervals during the 24-month study period. The primary analysis was based on the principle of intention to treat. The trial is registered with Current Controlled Trials, ISRCTN26666654. Findings: Between March 23, 2010, and Oct 21, 2011, we assessed 2188 participants for eligibility and recruited 424 patients from 95 general practices. 212 patients were randomly assigned to MBCT-TS and 212 to maintenance antidepressants. The time to relapse or recurrence of depression did not differ between MBCT-TS and maintenance antidepressants over 24 months (hazard ratio 0·89, 95% CI 0·67–1·18; p=0·43), nor did the number of serious adverse events. Five adverse events were reported, including two deaths, in each of the MBCT-TS and maintenance antidepressants groups. No adverse events were attributable to the interventions or the trial. Interpretation: We found no evidence that MBCT-TS is superior to maintenance antidepressant treatment for the prevention of depressive relapse in individuals at risk for depressive relapse or recurrence. Both treatments were associated with enduring positive outcomes in terms of relapse or recurrence, residual depressive symptoms, and quality of life. Funding: National Institute for Health Research (NIHR) Health Technology Assessment (HTA) programme, and NIHR Collaboration for Leadership in Applied Health Research and Care South West Peninsula.